Flow/acoustic interactions in porous media under a turbulent wind environment - Xu, Ying (Kansas State University, 2010)
Windscreens are widely used in outdoor microphone measurement for acoustic sensing systems. In many cases of outdoor microphone applications, wind noise interferes with the signals. The performance of measurement microphones thus heavily depends on correct designs of windscreens that are used to maximize the signal to noise ratio of the sensing system. The purpose of the study is to investigate the wind noise reduction between the unscreened microphone and the screened microphone under different frequencies of incoming wind turbulence. In this study, a modified immersed boundary method using the distributed forcing term has been applied to simulate the flow/acoustic interaction between air and the porous medium. Because of the high accuracy requirement in the vicinity of the interface between air and the porous medium, spatial derivatives of flux need to be discretized using high order schemes. In this study, several different schemes have been tested in the vicinity of the interface including a second-order upwind scheme, a third-order upwind scheme, and a fifth-order Weighted Essentially Non-Oscillatory (WENO) scheme. Based on the test results, the fifth-order WENO scheme is selected for most of the simulation cases. The model equations for flow outside the windscreen are the Navier-Stokes equations; flow inside the windscreen (porous medium) uses the modified Zwikker-Kosten equation. The wind turbulence in this study is generated by two different ways. The first is to place different sizes of solid cylinders and spheres in the upstream of the microphone under two-dimensional and three-dimensional conditions. The second is to use a Quasi-Wavelet method to generate the background atmospheric turbulence to simulate the real physical phenomena. Both two-dimensional and three-dimensional simulations for the flow over the unscreened and the screened microphone are presented and discussed under both low Reynolds number and high Reynolds number flow conditions. The results show that the windscreen effect is significant and the wind noise reduction level between the unscreened and the screened microphone can reach around 20dB either for low Reynolds number cases or for high Reynolds number cases. For low Reynolds number cases, Low flow resistivity windscreens are more effective for low frequency turbulence; high flow resistivity windscreens are more effective for high frequency turbulence. For high Reynolds number cases, the medium flow resistivity windscreens perform better compared to low flow resistivity windscreens and high flow resistivity windscreens.
Keywords: Wind noise; Windscreen; Porous media; Atmospheric turbulence; Flow resistivity; Engineering, Mechanical (0548)